IMPLEMENTASI KEBIJAKAN PEMERINTAH PROVINSI BALI DALAM MORATORIUM PEMBANGUNAN INFRASTRUKTUR AKOMODASI PARIWISATA HOTEL DI KABUPATEN BADUNG - Mastuty, Imma Triana; Noak, Piers Andreas; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2015)
ABSTRACK The rapid tourism development in Badung Regency as international destination requires the development of tourism accommodation that continous to grow. The provision of hotel accommodation facilities to support tourism activities is a priority to support of tourism development in the Badung Regency. The massive growth of hotel accommodation in Badung Regency is causing uncontrolled development of hotel accommodation and many hotel become overcapacities. So, the Bali provincial government issued a policy for temporary suspension of investment in the field of hotel accommodation services. Based on this problem, the aim of this research is to determine the affectiveness of moratorium hotel construction that has been implemented by Bali Government Province. The aim of moratorium policy is expected to result an order in development of tourism accommodation. This research is using descriptive-qualitative method. The data of this research is conduting by field observation to see real phenomenon and by in-depth interviews to know about moratorium policy in Badung Regency The conclusion of this research is the factors that lead to the ineffectiveness of the moratorium hotel policy in Badung Regency is caused by communication, resources, dispotition and bureaucratic structures that are not running optimally Keyword : implementation, sustainable development